Beyond carbonate biomineralization: why prokaryote-driven CO2 sequestration demands holistic evaluation - Schinteie, Richard; Nagaraj, Veena; Stalker, Linda; Tran-Dinh, Nai; Midgley, David J. (Frontiers in Bioengineering and Biotechnology, 2025)
Microbially induced carbonate precipitation (MICP) offers a promising biological approach to sequester atmospheric CO2 as stable mineral carbonates, mitigating climate change impacts. This perspective highlights the complexity underpinning prokaryote-driven biomineralization processes, emphasizing the necessity for holistic evaluation beyond simple carbonate formation. Key metabolic pathways such as carbonic anhydrase-mediated CO2 hydration, ureolysis, photosynthesis, and sulfate reduction contribute variably to mineral precipitation and the carbon footprint. Furthermore, calcium carbonate polymorphs with varying stability forms can affect carbon storage durability, while net carbon sequestration estimates often overlook critical factors including respiratory CO2 release, growth phases, and embodied emissions in microbial nutrient substrates. Finally, differentiating between transient microbial organic carbon and long-term mineral carbon storage is essential for accurate carbon accounting. Lifecycle carbon footprints vary significantly with metabolic strategies and substrate choices, impacting sustainable application prospects. Advancing MICP as an effective carbon removal technology requires integrated assessment of microbial physiology, environmental interactions, and process lifecycle emissions to optimize CO2 drawdown with environmental and economic viability.